HUBUNGAN KUALITAS PELAYANAN, CITRA SEKOLAH, LOYALITAS SISWA DAN KEPUTUSAN MEMILIH SEKOLAH - Dian Sudiantini; Kardinah Indrianna Meutia; Bintang Narpati; Farhan Saputra (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2023)
This study aims to analyze the effect of school service quality on guardian student loyalty, to analyze the effect of school image on student guardian loyalty and to analyze the effect of guardian student loyalty on parents' decision to choose. The data analysis used in this research is Partial Least Square (PLS). Guidelines in PLS-Parth. The hypothesis in this study is that there is a positive relationship between service quality and student guardian loyalty. There is a positive relationship between school image and student guardian loyalty. There is a positive relationship between service quality and parents' decision to choose. There is a positive relationship between school image and parents' decision to choose. There is a positive relationship between student guardian loyalty and parents' decision to choose.